2017
DOI: 10.1002/pssc.201600258
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and electrical response of flexible supercapacitor based on activated carbon from bamboo

Abstract: We present the fabrication and electrical response of a flexible prototype supercapacitor based on activated carbon electrodes obtained from bamboo (Guadua angustifolia Kunth) as precursor. The supercapacitor prototype was fabricated by using a multilayer configuration method; activated carbon electrodes were impregnated with 0.5 M H2SO4 as electrolyte and filter paper was used as separator. Carbon activation was performed by using NaOH and KOH solutions. Activated carbon electrodes were characterized by adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Based on the EDS test data, the silica content produced tends to be still high at 0.2% so that it affects the carbon element content formed as shown in Based on Figure 2, there is a difference in the width of the CV curve for each sample at the same scan rate of 1 mV/s. The wider the CV curve indicates the higher the specific capacitance value of the sample being tested, while the higher the slope of the CV curve indicates the greater the sample resistance value [10], [11], [13], [15], [16], [17]. In addition, the addition of AB causes the width of the CV curve to increase.…”
Section: Figure 1 Sem Image At 10000× Magnificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the EDS test data, the silica content produced tends to be still high at 0.2% so that it affects the carbon element content formed as shown in Based on Figure 2, there is a difference in the width of the CV curve for each sample at the same scan rate of 1 mV/s. The wider the CV curve indicates the higher the specific capacitance value of the sample being tested, while the higher the slope of the CV curve indicates the greater the sample resistance value [10], [11], [13], [15], [16], [17]. In addition, the addition of AB causes the width of the CV curve to increase.…”
Section: Figure 1 Sem Image At 10000× Magnificationmentioning
confidence: 99%
“…Biomass waste is activated chemically using chemical activator or physically at high temperature to be converted into activated carbon. This activated carbon will then be used as a medium for making supercapacitor electrodes [8], [9], [10], [11], [12]. However, studies on the utilization of biomass waste from pepper peels have not been widely reported.…”
Section: Introductionmentioning
confidence: 99%
“…The historical development of supercapacitors can be divided into three primary stages according to the type of electrode materials and their mechanism of charge storage and transfer. 16 The first of these is the electric double layer capacitors (EDLCs), in which the electrode materials are primarily carbon-based, such as activated carbon, 17–22 carbon aerogel, 23–28 carbon nanotubes, 29–34 and carbon nanofibers. 35–42 The EDLCs store charge electrostatically, which does not include the transfer of charge between the electrode and electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Activated carbon can be derived from a wide range of raw materials. Common precursor materials for preparing activated carbon include wood materials (including all types of wood [ 52 , 53 , 54 ], bamboo [ 55 , 56 , 57 ], and starch [ 58 , 59 , 60 ]), waste from agricultural and food industries (such as coconut shell [ 61 , 62 , 63 ], walnut shell [ 64 , 65 ], cocoa shell [ 66 , 67 ], banana peel [ 68 , 69 , 70 ], peanut peel [ 71 , 72 ], rice husks [ 73 , 74 ], bagasse [ 75 , 76 ], and tea leaves [ 77 , 78 ]), coal-based materials (anthracite [ 79 , 80 ], bitumen [ 81 , 82 ], and lignite [ 83 , 84 , 85 ]), petroleum materials (petroleum coke [ 50 , 51 , 52 , 86 , 87 , 88 ], needle coke [ 53 , 54 , 55 , 89 , 90 ,…”
Section: Introductionmentioning
confidence: 99%